Cement-based capillary crystalline concrete with strong self-repairing property and preparation method thereof

By using cement-based permeable crystalline waterproof materials and organically modified sepiolite in concrete, forming hydrophobic layers and insoluble crystals, the problems of cracking and leakage of traditional concrete are solved, and efficient crack-resistant and anti-seepage performance and self-repair are achieved. Functional, extends the life of the structure and enhances safety and reliability.

CN119191780APending Publication Date: 2024-12-27DANGYANG ZHONGYANG BUILDING MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411198523.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional high-performance concrete is prone to cracking in areas with dense steel bar layout and concentrated stress, resulting in a reduced load capacity of the structure, corrosion resistance and permeability. The existing crack-proof and permeability anti-permeability agents have failed to fundamentally solve the cracking and permeability of concrete. Leaked problem.

Method used

Develop a highly self-repairing cement-based permeable crystalline concrete, using cement, sand, gravel, fly ash, silica fume, water reducing agent, exciter, defoaming agent, ramie fiber, basalt fiber through precise ratio , CaCO3 whiskers, organically modified sepiolite and cement-based permeable crystalline waterproof materials form hydrophobic layers and insoluble crystals, prevent moisture from penetration and fill microcracks, and realize self-healing function.

Benefits of technology

It significantly improves the anti-cracking and anti-seepage properties of concrete and self-repairing capabilities, extends the service life of the structure, enhances its safety and reliability, and ensures stability and durability in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses cement-based capillary crystalline concrete with strong self-repairing property and a preparation method thereof. The concrete comprises the following raw materials in parts by weight: 450-550 parts of cement; 800 to 900 parts of sand; 1050 to 1050 parts of broken stone; 95 to 105 parts of fly ash; 38 to 50 parts of silica fume; 145 to 160 parts of water; 15 to 20 parts of a water reducing agent; 16-19 parts of an exciting agent; 3 to 4.5 parts of a defoaming agent; 13-17 parts of a shrinkage reducing agent; 7-9 parts of ramie fiber; 11 to 15 parts of basalt fiber; 22 to 26 parts of CaCO3 crystal whiskers; 20 to 30 parts of organic modified sepiolite; and 60-90 parts of a cement-based capillary crystalline waterproof material. The concrete provided by the invention has the advantages of high compressive strength and excellent anti-cracking and anti-seepage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building material technology, and in particular to a highly self-repairing cement-based permeable crystalline concrete and a preparation method thereof. Background Art

[0002] At present, the layered pouring method of high-performance concrete is widely used in the construction of immersed tube tunnels. However, although high-performance concrete has high strength and durability, due to its relatively low tensile strength and toughness, it often cracks in areas where the steel bars are densely arranged and stress is concentrated. Such cracks will not only reduce the load-bearing capacity of the concrete structure, but also seriously affect its corrosion resistance and impermeability, thereby reducing the service life of the concrete and posing a threat to the safety of the structure. In the past, it was generally believed that the shrinkage of concrete was the main cause of cracking, so attempts were made to compensate for the volume shrinkage of concrete by adding anti-cracking and anti-permeability agents with expansion functions such as silica fume and fly ash to the concrete. However, these traditional anti-cracking and anti-permeability agents do not fundamentally solve the problems of concrete cracking and leakage. Existing studies have pointed out that the volume shrinkage of concrete is not the only cause of cracking, but also involves factors such as the tensile strength, elastic modulus and creep relaxation of the material itself, as well as external factors such as the design of structural components, constraints and changes in ambient temperature and humidity. Therefore, it is difficult to effectively solve the problems of concrete cracking and leakage only from the perspective of compensating for the volume shrinkage of concrete. This shows that there is an urgent need to develop new high-performance anti-cracking and anti-seepage agents for concrete to meet this challenge. Summary of the invention

[0003] In order to solve at least one of the above technical problems, a cement-based permeable crystalline concrete with high compressive strength, excellent crack resistance and anti-seepage performance is developed, and it has self-repairing properties. The present application provides a cement-based permeable crystalline concrete with strong self-repairing properties and a preparation method thereof. In a first aspect, the present application provides a highly self-repairing cement-based permeable crystalline concrete, wherein the concrete comprises the following raw materials by weight: 450-550 parts of cement; Sand 800-900 parts; 1050-1150 parts of crushed stone; Fly ash 95-105 parts; Silica fume 38-50 parts; 145-160 parts of water; 15-20 parts of water reducing agent; 16-19 parts of stimulant; 3-4.5 parts of defoaming agent; 13-17 parts of shrinkage reducing agent; 7-9 parts of ramie fiber; Basalt fiber 11-15 parts; 22-26 parts of CaCO3 whiskers; 20-30 parts of organic modified sepiolite; 60-90 parts of cement-based penetrating crystalline waterproof material.

[0004] By adopting the above technical scheme, the present application provides a cement-based permeable crystalline concrete with strong self-repairing performance, the purpose of which is to solve the problem that traditional concrete is prone to cracking and leakage. The concrete not only has high strength and durability by accurately proportioning various raw materials, but also has a unique self-repairing function. Among them, cement, as a basic cementitious material, constructs the basic skeleton and strength of concrete; sand and gravel, as aggregates, enhance the mechanical properties and stability of concrete; fly ash and silica fume, as active admixtures, improve the workability and microstructure of concrete, and improve its density and durability; water reducer reduces the amount of water in the concrete mixture, thereby improving the strength and impermeability of concrete; activator helps to accelerate the process of cement hydration and improve the early strength of concrete; defoamer reduces bubbles in concrete and improves the density of concrete; shrinkage reducer reduces the shrinkage of concrete and reduces the possibility of cracking; ramie fiber and basalt fiber, as reinforcing materials, increase the toughness and crack resistance of concrete; CaCO3 whisker, as a slender inorganic filler, helps to form a more compact microstructure and improve the impermeability of concrete.

[0005] Silicone-modified sepiolite is an important additive that changes the surface properties of sepiolite by combining with silicone, making it hydrophobic. This allows the modified sepiolite to form a hydrophobic layer inside the concrete, preventing water penetration while maintaining a good microstructure. When concrete is subjected to external forces and microcracks are generated, these silicone-modified sepiolite particles can prevent water from entering the cracks through physical and chemical effects, thereby reducing the erosion of water inside the concrete and helping to maintain the integrity of the concrete. Cement-based penetrating crystalline waterproofing material is a material containing a special crystal generator that can generate insoluble crystals inside the concrete, fill the pores and microcracks in the concrete, and effectively prevent the penetration of water and other harmful substances. These crystals will grow as the internal environment of the concrete changes, continue to develop in a humid environment, and further enhance the anti-seepage performance and durability of the concrete. In summary, by adopting the above formula and technical solutions, this new type of concrete can not only significantly improve the overall stability and durability of the structure, but also effectively reduce the risk of cracking caused by changes in the external environment, extend the service life of the structure, and enhance its safety and reliability.

[0006] Optionally, the weight ratio of the organic modified sepiolite to the cement-based permeable crystalline waterproof material is 1:(2.7-3.4).

[0007] By adopting the above technical scheme, the present invention effectively improves the anti-cracking and anti-seepage performance of concrete materials. Specifically, organically modified sepiolite and cement-based penetrating crystalline waterproof material are used in a weight ratio of 1: (2.7-3.4). After surface modification, the organically modified sepiolite has good hydrophobicity, which enables it to form a stable hydrophobic protective layer inside the concrete, thereby effectively reducing the penetration of water and reducing the internal stress caused by water, thereby reducing the occurrence and development of microcracks inside the concrete. At the same time, cement-based penetrating crystalline waterproof material can penetrate into the pores and microcracks of concrete, and generate insoluble crystals under appropriate humidity conditions. These crystals can block the capillary channels and microcracks inside the concrete, enhance the overall density of the concrete, and further improve its anti-seepage performance. When the concrete structure is subjected to external forces to produce new microcracks, these crystals will continue to grow and fill the cracks, showing good self-healing function, thereby effectively preventing moisture from entering the concrete through the newly generated cracks. In summary, through the synergistic effect of the two materials, the present invention significantly improves the crack resistance and anti-seepage performance of concrete, ensuring the stability and durability of the concrete structure under various environmental conditions.

[0008] Optionally, the weight ratio of the organic modified sepiolite to the cement-based permeable crystalline waterproof material is 1:3.

[0009] Optionally, the total weight of the organic modified sepiolite and the cement-based permeable crystalline waterproof material accounts for 3-4% of the total weight of the concrete.

[0010] Optionally, the preparation method of the organically modified sepiolite is as follows: A1. After drying the sepiolite at 110-150° C. for 10-20 hours, the mixture is placed in a thoroughly dried and anhydrous reactor, and then anhydrous ethanol is added. The stirring rate is controlled at 300-650 rpm, and the temperature is raised and kept constant at 50-80° C. Then 3-aminopropyltrimethoxysilane is added. The ethanol in the reactor is kept under condensation and reflux. The reaction is stirred at a constant temperature for 6-10 hours, and then centrifuged. The obtained solid is placed in a vacuum oven and dried at 40-55° C. for 8-13 hours to obtain organosilicon-modified sepiolite. A2. Place the organosilicon-modified sepiolite in a completely dry and water-free vacuum-sealed reactor, continuously evacuate the reactor to maintain the pressure in the reactor within the range of 0.095-0.1 MPa, and maintain the negative pressure for 13-20 hours. Then, inject epoxy silane into the reactor by means of the negative pressure. After the epoxy silane completely immerses the organosilicon-modified sepiolite in the reactor, stop injecting epoxy silane. After standing in a sealed state for 4-9 hours, transfer the material in the reactor to a sealed and dry centrifuge, centrifuge, and separate the solid, which is the organic modified sepiolite. Put it into a drying container for temporary storage.

[0011] By adopting the above technical scheme, the preparation method of the organic modified sepiolite provided by the present application realizes the effective modification of sepiolite, thereby significantly improving the anti-cracking and anti-seepage performance of concrete materials. Specifically, sepiolite is modified twice, first modified with 3-aminopropyltrimethoxysilane, and second modified with epoxysilane, and such a treatment method is to give full play to the performance advantages of sepiolite in concrete. The purpose of the first modification using 3-aminopropyltrimethoxysilane is to introduce hydrophobic organosilicon groups to the surface of sepiolite, change its original hydrophilic properties, and make sepiolite have better hydrophobicity and compatibility with cement matrix. This modification process chemically reacts with the hydroxyl groups on the surface of sepiolite through a silane coupling agent to form a strong chemical bond, thereby enhancing the interfacial bonding between sepiolite and the concrete matrix. The second modification using epoxysilane is to further enhance the chemical stability of sepiolite and form a more stable hydrophobic layer on the surface of sepiolite. Epoxysilane can react chemically with the amino group introduced during the first modification to form a cross-linked structure, further improving the durability and stability of sepiolite. Through this step, the composite coating formed on the surface of sepiolite is not only hydrophobic, but also has higher chemical stability, and can play a better waterproof role inside the concrete. Chemical reactions did occur between the chemical components used in the two modification processes. During the first modification, 3-aminopropyltrimethoxysilane reacted with the hydroxyl groups on the surface of sepiolite to form Si-O-Si bonds, fixing the organosilicon groups on the surface of sepiolite. During the second modification, epoxysilane reacted with the amino group introduced during the first modification to form a more stable cross-linked structure, which improved the chemical stability of sepiolite. Through the two modifications, sepiolite has better hydrophobicity and chemical stability, and can form a stable hydrophobic protective layer inside the concrete, reduce water penetration, and reduce the stress caused by water changes inside the concrete, thereby reducing the risk of concrete cracking. In addition, the modified sepiolite can also form a stable protective layer inside the concrete, reduce the development of microcracks, and further improve the overall density and anti-seepage performance of the concrete. Therefore, when this modified sepiolite is used in combination with cement-based penetrating crystalline waterproof materials, it can significantly improve the crack resistance and anti-seepage performance of concrete structures, ensuring the stability and durability of concrete in complex environments.

[0012] Optionally, the cement-based penetrating crystalline waterproof material includes the following raw materials by weight: 35-65 parts of silicate cement, 22-28 parts of fly ash beads, 10-20 parts of zeolite powder, 10-15 parts of calcium oxide expansion agent, 10-15 parts of magnesium oxide expansion agent, 8-13 parts of retarder, 8-15 parts of dodecyl ethoxy sulfobetaine, 9-15 parts of meso-tartaric acid, and 612 parts of sodium citrate.

[0013] By adopting the above technical scheme, the cement-based permeable crystalline waterproof material provided by the present invention achieves significant improvement in the crack resistance and anti-seepage performance of concrete structures by accurately proportioning raw materials such as silicate cement, fly ash beads, zeolite powder, calcium oxide expansion agent, magnesium oxide expansion agent, retarder, dodecyl ethoxy sulfobetaine, meso-tartaric acid and sodium citrate. Specifically, silicate cement, as the basic cementitious material, provides the basic skeleton and strength of concrete; fly ash beads and zeolite powder, as active admixtures, improve the workability and microstructure of concrete, and increase its density and durability; calcium oxide expansive agent and magnesium oxide expansive agent compensate for the volume shrinkage of concrete through expansion, reducing the risk of cracking; retarder slows down the hydration rate of cement, helps to better control the concrete hardening process, and improves the homogeneity and density of concrete; dodecyl ethoxy sulfobetaine, as a high-efficiency water reducer, reduces the amount of water in the concrete mixture and improves the strength and impermeability of concrete; meso-tartaric acid and sodium citrate, as shrinkage reducers and regulators, further reduce the shrinkage of concrete and improve its stability.

[0014] This carefully proportioned cement-based permeable crystalline waterproof material can generate insoluble crystals inside the concrete, filling the pores and micro-cracks in the concrete, effectively preventing the penetration of water and other harmful substances. These crystals will grow as the internal environment of the concrete changes, and continue to develop in a humid environment, further enhancing the anti-seepage performance and durability of the concrete. Therefore, this waterproof material can not only significantly improve the overall stability and durability of the structure, but also effectively reduce the risk of cracking caused by changes in the external environment, extend the service life of the structure, and enhance its safety and reliability.

[0015] Optionally, the preparation method of the cement-based permeable crystalline waterproof material is as follows: B1. Weigh each raw material component according to the raw material ratio and set aside; B2. Add the weighed silicate cement, fly ash beads, zeolite powder, calcium oxide expansion agent, magnesium oxide expansion agent, retarder, dodecylethoxysulfobetaine and meso-tartaric acid into a ball mill and grind evenly to obtain a permeable crystallization type high performance concrete anti-cracking and anti-seepage agent.

[0016] By adopting the above technical solution, the preparation method produces a cement-based permeable crystalline waterproof material that can significantly improve the stability and durability of concrete structures through precise batching and efficient grinding and mixing processes. This material can effectively prevent water penetration and reduce concrete cracking, thereby extending the service life of the building.

[0017] Optionally, the ball milling process conditions of step B2 are: ball-to-material ratio of 8:1, grinding ball particle size of 10-20 mm, ball mill speed of 150 r / min, and ball milling time of 20-30 min.

[0018] In a second aspect, the present application provides a method for preparing a cement-based permeable crystallized concrete with strong self-repairability, the method for preparing the concrete comprising the following steps: S1, divide the water into four equal parts; and mix the first part of water with cement, sand, gravel, fly ash, silica fume, CaCO3 whisker, organic modified sepiolite, and cement-based permeable crystalline waterproof material to obtain a first mixture; S2, the second portion of water is mixed with the activator, and the first portion of the mixture prepared in step S1 is added, and then ramie fiber and basalt fiber are added and mixed evenly to prepare the second mixture. S3, mixing the third portion of water with the water reducing agent, adding the mixture to the second portion of the mixture and mixing evenly to obtain a third mixture; S4. Evenly mix the fourth portion of water with the defoamer and the shrinkage reducer, and add the mixture to the third portion of the mixture, mix evenly to obtain a concrete mixture, and cast and cure the concrete mixture to obtain a self-repairing cement-based permeable crystalline concrete.

[0019] By adopting the above technical solution, the present application effectively improves the anti-cracking and anti-seepage performance and self-repairing ability of concrete, ensures the stability and durability of concrete structures in complex environments, extends the service life of the structure, and enhances its safety and reliability.

[0020] Optionally, the curing is as follows: first, under the conditions of a temperature of 20-30°C and a humidity of 80-90%, the curing time is 7-10 days, and then under the conditions of a temperature of 23±2°C and a humidity of 50-60%, the curing time is at least 21 days.

[0021] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The present application provides a cement-based permeable crystalline concrete with strong self-repairing properties, the purpose of which is to solve the problem that traditional concrete is prone to cracking and leakage. The concrete not only has high strength and durability through precise proportioning of various raw materials, but also has a unique self-repairing function. Among them, cement, as a basic cementitious material, constructs the basic skeleton and strength of concrete; sand and gravel, as aggregates, enhance the mechanical properties and stability of concrete; fly ash and silica fume, as active admixtures, improve the workability and microstructure of concrete, and improve its density and durability; water reducer reduces the amount of water in the concrete mixture, thereby improving the strength and impermeability of concrete; activator helps to accelerate the process of cement hydration and improve the early strength of concrete; defoamer reduces bubbles in concrete and improves the density of concrete; shrinkage reducer reduces the shrinkage of concrete and reduces the possibility of cracking; ramie fiber and basalt fiber, as reinforcing materials, increase the toughness and crack resistance of concrete; CaCO3 whiskers, as a slender inorganic filler, help to form a denser microstructure and improve the impermeability of concrete.

[0022] Silicone-modified sepiolite is an important additive that changes the surface properties of sepiolite by combining with silicone, making it hydrophobic. This allows the modified sepiolite to form a hydrophobic layer inside the concrete, preventing water penetration while maintaining a good microstructure. When concrete is subjected to external forces and microcracks are generated, these silicone-modified sepiolite particles can prevent water from entering the cracks through physical and chemical effects, thereby reducing the erosion of water inside the concrete and helping to maintain the integrity of the concrete. Cement-based penetrating crystalline waterproofing material is a material containing a special crystal generator that can generate insoluble crystals inside the concrete, fill the pores and microcracks in the concrete, and effectively prevent the penetration of water and other harmful substances. These crystals will grow as the internal environment of the concrete changes, continue to develop in a humid environment, and further enhance the anti-seepage performance and durability of the concrete. In summary, by adopting the above formula and technical solutions, this new type of concrete can not only significantly improve the overall stability and durability of the structure, but also effectively reduce the risk of cracking caused by changes in the external environment, extend the service life of the structure, and enhance its safety and reliability.

[0023] 2. This application effectively improves the anti-cracking and anti-seepage performance and self-repairing ability of concrete, ensures the stability and durability of concrete structures in complex environments, extends the service life of the structure, and enhances its safety and reliability. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments.

[0025] Fly ash beads: Henan Jinrun New Materials Co., Ltd. Product No. JR1005.

[0026] Zeolite powder: CAS No. 1318-02-1, content 98%.

[0027] Calcium oxide expansion agent: Guangxi Nanning Gaohong Herun Building Materials Technology Co., Ltd.

[0028] Magnesium oxide expansion agent: Yingkou Nanlou Economic Development Zone Qiaoxu Magnesium Materials Factory, particle size 250 mesh.

[0029] Dodecyl ethoxy sulfobetaine: Shanghai Nosong Industrial Co., Ltd.

[0030] Meso-tartaric acid: CAS No. 5990-63-6, content 99.9%.

[0031] Sodium citrate: Jiangsu Caiwei Biotechnology Co., Ltd.

[0032] Boric acid: CAS No. 10043-35-3, content 99.9% po42.5 cement: Taizhou Yigao E-Commerce Co., Ltd.

[0033] Preparation Example 1 This preparation example provides a cement-based permeable crystalline waterproof material, which includes the following raw materials by weight: 35 parts of silicate cement (PO42.5 cement), 22 parts of fly ash beads, 10 parts of zeolite powder, 10 parts of calcium oxide expansion agent, 10 parts of magnesium oxide expansion agent, 8 parts of retarder, 8 parts of dodecyl ethoxy sulfobetaine, 9 parts of meso-tartaric acid, and 6 parts of sodium citrate.

[0034] The retarder in this preparation example is selected from boric acid.

[0035] The preparation method of cement-based permeable crystalline waterproof material is as follows: B1. Weigh each raw material component according to the raw material ratio and set aside; B2. Add the weighed silicate cement, fly ash beads, zeolite powder, calcium oxide expansion agent, magnesium oxide expansion agent, retarder, dodecylethoxysulfobetaine and meso-tartaric acid into a ball mill and grind evenly to obtain a permeable crystallization type high performance concrete anti-cracking and anti-seepage agent.

[0036] The ball milling process conditions in step B2 are: ball-to-material ratio of 8:1, grinding ball particle size of 10 mm, ball mill speed of 150 r / min, and ball milling time of 20 min.

[0037] Preparation Example 2 This preparation example provides a cement-based permeable crystalline waterproof material, which includes the following raw materials by weight: 55 parts of silicate cement, 26 parts of fly ash beads, 17 parts of zeolite powder, 14 parts of calcium oxide expansion agent, 13 parts of magnesium oxide expansion agent, 11 parts of retarder, 13 parts of dodecyl ethoxy sulfobetaine, 13 parts of meso-tartaric acid, and 10 parts of sodium citrate.

[0038] The retarder in this preparation example is selected from boric acid.

[0039] The preparation method of cement-based permeable crystalline waterproof material is as follows: B1. Weigh each raw material component according to the raw material ratio and set aside; B2. Add the weighed silicate cement, fly ash beads, zeolite powder, calcium oxide expansion agent, magnesium oxide expansion agent, retarder, dodecylethoxysulfobetaine and meso-tartaric acid into a ball mill and grind evenly to obtain a permeable crystallization type high performance concrete anti-cracking and anti-seepage agent.

[0040] The ball milling process conditions in step B2 are: ball-to-material ratio of 8:1, grinding ball particle size of 17 mm, ball mill speed of 150 r / min, and ball milling time of 18 min.

[0041] Preparation Example 3 This preparation example provides a cement-based permeable crystalline waterproof material, which includes the following raw materials by weight: 65 parts of Portland cement, 28 parts of fly ash beads, 20 parts of zeolite powder, 15 parts of calcium oxide expansion agent, 15 parts of magnesium oxide expansion agent, 13 parts of retarder, 15 parts of dodecyl ethoxy sulfobetaine, 15 parts of meso-tartaric acid, and 12 parts of sodium citrate.

[0042] The retarder in this preparation example is selected from boric acid.

[0043] The preparation method of cement-based permeable crystalline waterproof material is as follows: B1. Weigh each raw material component according to the raw material ratio and set aside; B2. Add the weighed silicate cement, fly ash beads, zeolite powder, calcium oxide expansion agent, magnesium oxide expansion agent, retarder, dodecylethoxysulfobetaine and meso-tartaric acid into a ball mill and grind evenly to obtain a permeable crystallization type high performance concrete anti-cracking and anti-seepage agent.

[0044] The ball milling process conditions in step B2 are: ball-to-material ratio of 8:1, grinding ball particle size of 20 mm, ball mill speed of 150 r / min, and ball milling time of 30 min.

[0045] Example 1 This embodiment provides a strong self-repairing cement-based permeable crystalline concrete, which includes the following raw materials by weight: 450 parts of cement; 800 parts of sand; 1050 parts of crushed stone; 95 parts of fly ash; 38 parts of silica fume; 145 parts of water; 15 parts of water reducer; 16 parts of activator; 3 parts of defoamer; 13 parts of shrinkage reducer; 7 parts of ramie fiber; 11 parts of basalt fiber; 22 parts of CaCO3 whisker; 26 parts of organic modified sepiolite; 78 parts of cement-based permeable crystalline waterproof material. The cement-based permeable crystalline waterproof material in this preparation example is prepared by Preparation Example 1.

[0046] The cement in this embodiment is po42.5 cement. The particle size of the crushed stone in this embodiment is that the crushed stone is selected from limestone and basalt crushed stone with good grading, dense and hard, and rough surface in a mass ratio of 1:1, and the particle size range is 5mm15mm. The crushed stones of continuous particle sizes of 510mm and 1015mm are mixed in a mass ratio of 5:5. The water reducer in this embodiment is a high-efficiency polycarboxylic acid water reducer. The activator in this embodiment is calcium chloride. The defoamer in this embodiment is a defoamer of Datian Chemical, model PT-5230. The shrinkage reducer in this embodiment is a P80 high-efficiency shrinkage reducer. The ramie fiber in this embodiment has a length of 4050mm and a diameter of 30μm40μm. The basalt fiber in this embodiment has a length of 12mm and a diameter of 7μm15μm.

[0047] The sand is made of hard river sand and well-graded high-quality quartz sand with a mass ratio of 8:2. The river sand fineness modulus is 2.83.0, the silica content in the quartz sand is not less than 98%, the particle size is 0.30.6mm, and the density is 2.62g / cm 3 .

[0048] The preparation method of the organically modified sepiolite in this embodiment is as follows: A1. After the sepiolite was dried at 130° C. for 15 hours, it was placed in a thoroughly dried and anhydrous reactor, and then anhydrous ethanol was added. The stirring rate was controlled at 600 rpm, and the temperature was raised and kept constant at 75° C. Then 3-aminopropyltrimethoxysilane was added. The ethanol in the reactor was kept under condensation and reflux. After constant temperature stirring and reaction for 8 hours, the reaction was centrifuged, and the obtained solid was placed in a vacuum oven and dried at 50° C. for 10 hours to obtain organosilicon-modified sepiolite; A2. Place the organosilicon-modified sepiolite in a completely dry and water-free vacuum-sealed reactor, continuously evacuate the reactor to maintain the pressure in the reactor within the range of 0.095-0.1 MPa. After maintaining the negative pressure for 15 hours, inject epoxy silane into the reactor by relying on the negative pressure. After the epoxy silane completely immerses the organosilicon-modified sepiolite in the reactor, stop injecting epoxy silane. After standing in a sealed state for 8 hours, transfer the material in the reactor to a sealed and dry centrifuge for centrifugal separation. The separated solid is the organic-modified sepiolite, which is placed in a drying container for temporary storage.

[0049] When preparing the organosilicon sepiolite, the weight ratio of anhydrous ethanol, sepiolite and 3-aminopropyltrimethoxysilane is 20:1:0.3.

[0050] The weight ratio of epoxysilane to sepiolite is 0.3:1.

[0051] The method for preparing concrete in this embodiment comprises the following steps: S1, divide the water into four equal parts; and mix the first part of water with cement, sand, gravel, fly ash, silica fume, CaCO3 whisker, organic modified sepiolite, and cement-based permeable crystalline waterproof material to obtain a first mixture; S2, the second portion of water is mixed with the activator, and the first portion of the mixture prepared in step S1 is added, and then ramie fiber and basalt fiber are added and mixed evenly to prepare the second mixture. S3, mixing the third portion of water with the water reducing agent, adding the mixture to the second portion of the mixture and mixing evenly to obtain a third mixture; S4. Evenly mix the fourth portion of water with the defoamer and the shrinkage reducer, and add the mixture to the third portion of the mixture, mix evenly to obtain a concrete mixture, and cast and cure the concrete mixture to obtain a self-repairing cement-based permeable crystalline concrete.

[0052] The curing is as follows: first, at a temperature of 30°C and a humidity of 90%, the curing time is 10 days, and then at a temperature of 23±2°C and a humidity of 58%, the curing time is 21 days.

[0053] Example 2 The difference between this embodiment and embodiment 1 is that when preparing the highly self-repairing cement-based permeable crystalline concrete, the total weight of the organic modified sepiolite and the cement-based permeable crystalline waterproof material is 104 parts, and the weight ratio of the organic modified sepiolite to the cement-based permeable crystalline waterproof material is 1:2.7.

[0054] Example 3 The difference between this embodiment and embodiment 1 is that when preparing the highly self-repairing cement-based permeable crystalline concrete, the total weight of the organic modified sepiolite and the cement-based permeable crystalline waterproof material is 104 parts, and the weight ratio of the organic modified sepiolite to the cement-based permeable crystalline waterproof material is 1:3.2.

[0055] Example 4 The difference between this embodiment and embodiment 1 is that when preparing the highly self-repairing cement-based permeable crystalline concrete, the total weight of the organic modified sepiolite and the cement-based permeable crystalline waterproof material is 104 parts, and the weight ratio of the organic modified sepiolite to the cement-based permeable crystalline waterproof material is 1:3.4.

[0056] Comparative Examples 1-3 Comparative Example 1 The difference between this comparative example and Example 1 is that when preparing the cement-based permeable crystalline concrete with strong self-repairing properties, an equal amount of organically modified sepiolite is used to replace the cement-based permeable crystalline waterproof material.

[0057] Comparative Example 2 The difference between this comparative example and Example 1 is that when preparing the cement-based permeable crystalline concrete with strong self-repairing properties, an equal amount of cement-based permeable crystalline waterproof material is used to replace the organic modified sepiolite.

[0058] Comparative Example 3 The difference between this comparative example and Example 1 is that when preparing the cement-based permeable crystalline concrete with strong self-repairing properties, an equal amount of sepiolite is used instead of the organosilicon-modified sepiolite.

[0059] Experimental testing: 1. Compressive strength: According to GB / T500812019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the compressive strength of the sample is tested.

[0060] 2. Anti-seepage pressure (28d / Mpa): Anti-seepage pressure is tested in accordance with GB / T 50082-2009.

[0061] 3. Antifreeze performance: According to the standard JGJ / T193 "Concrete Durability Test and Evaluation Standard", the antifreeze grades of the products obtained in Examples 1-4 and Comparative Examples 1-3 were measured.

[0062] The experimental test results of Examples 1-4 and Comparative Examples 1-3 are shown in Table 1.

[0063] Table 1 - Experimental test results of Examples 1-4 and Comparative Examples 1-3 Example Compressive strength (28d) Impermeability pressure (28d) Mpa Antifreeze performance (quick freezing method) Example 1 125.7 2.5 F350 Example 2 122.7 2.1 F350 Example 3 124.6 2.3 F350 Example 4 123.8 2.2 F350 Comparative Example 1 118.9 1.8 F300 Comparative Example 2 120.7 1.7 F300 Comparative Example 3 117.4 1.5 F250 Result analysis: The difference between Examples 2-4 and Example 1 is that when preparing the strong self-repairing cement-based permeable crystalline concrete, the weight ratio of organic modified sepiolite and cement-based permeable crystalline waterproof material is different. Combined with the experimental test data in Table 1, it can be seen that when the weight ratio of organic modified sepiolite and cement-based permeable crystalline waterproof material is 1:3, the comprehensive performance of the obtained strong self-repairing cement-based permeable crystalline concrete is better. The difference between Comparative Example 1 and Example 1 is that when preparing the strong self-repairing cement-based permeable crystalline concrete, an equal amount of organic modified sepiolite is used to replace the cement-based permeable crystalline waterproof material. The difference between Comparative Example 2 and Example 1 is that when preparing the strong self-repairing cement-based permeable crystalline concrete, an equal amount of cement-based permeable crystalline waterproof material is used to replace the organic modified sepiolite. Combined with the experimental test data in Table 1, it can be seen that when cement-based permeable crystalline waterproof material and organic modified sepiolite are used at the same time, it has a significant effect on improving the compressive strength and impermeability of concrete. The difference between Comparative Example 3 and Example 1 is that, when preparing a cement-based permeable crystalline concrete with strong self-repairability, an equal amount of sepiolite is used instead of organosilicon-modified sepiolite. It can be seen from the experimental test data in Table 1 that when unmodified sepiolite is used, the compressive strength, impermeability and crack resistance of the concrete will be affected. The reason may be that the surface of unmodified sepiolite usually has a strong hydrophilicity, which may cause it to be poorly dispersed in concrete and not tightly bonded to the cement matrix, thereby affecting the microstructure and overall performance of the concrete. In contrast, the surface of sepiolite modified by organosilicon is hydrophobic, which helps to improve its dispersibility in concrete and its interfacial bonding with the cement matrix, thereby improving the comprehensive performance of the concrete.

[0064] Embodiment 5-6 The difference between Example 5-6 and Example 1 is that when preparing the cement-based permeable crystalline concrete with strong self-repairability, the weight proportions of some components are changed. The differences are shown in Table 2.

[0065] Table 2 - Differences between Example 5-6 and Example 1 The experimental test results of Examples 5-6 are shown in Table 3.

[0066] Table 3 - Experimental test results of Examples 5-6 Example Compressive strength (28d) Impermeability pressure (28d) Mpa Antifreeze performance (quick freezing method) Example 1 125.7 2.5 F350 Example 5 128.9 2.9 F400 Example 6 126.7 2.7 F350 Result analysis: The difference between Example 5-6 and Example 1 is that when preparing the strong self-repairing cement-based permeable crystallization concrete, the weight proportions of some components are different. Combined with the experimental test results in Table 3, it can be seen that the comprehensive performance of the strong self-repairing cement-based permeable crystallization concrete prepared by Example 5 is better.

[0067] Embodiment 7-11 The difference between Examples 7-11 and Example 5 is that when preparing the highly self-repairing cement-based permeable crystalline concrete, on the premise that the weight ratio of the organic modified sepiolite and the cement-based permeable crystalline waterproof material is 1:3, the total weight ratio of the organic modified sepiolite and the cement-based permeable crystalline waterproof material in the highly self-repairing cement-based permeable crystalline concrete is changed, and the optimal weight ratio is selected.

[0068] In Example 5, the total weight of the organically modified sepiolite and the cement-based permeable crystalline waterproof material is 104 parts, and the total weight of the highly self-repairing cement-based permeable crystalline concrete is 3056 parts.

[0069] Therefore, it is not difficult to conclude that in Example 5, the proportion of organically modified sepiolite (referred to as variable 1) and cement-based permeable crystalline waterproof material (referred to as variable 2) in the highly self-repairing cement-based permeable crystalline concrete (referred to as the matrix) is 3.40%.

[0070] The differences between Examples 7-11 and Example 5 are shown in Table 4.

[0071] Proportion = (variable 1 + variable 2) / total weight of matrix * 100%.

[0072] Table 4 - Differences between Examples 7-11 and Example 5 The experimental test results of Examples 7-11 are shown in Table 5.

[0073] Table 5 - Experimental test results of Examples 7-11 Example Compressive strength (28d) Impermeability pressure (28d) Mpa Antifreeze performance (quick freezing method) Example 5 128.9 2.9 F400 Example 7 126.5 2.6 F350 Example 8 127.3 2.7 F350 Example 9 127.9 2.8 F400 Example 10 129.7 3.2 F400 Embodiment 11 129.4 3.1 F400 Result analysis: The difference between Example 7-11 and Example 5 is that when preparing the strong self-repairing cement-based permeable crystalline concrete, the total weight of the organic modified sepiolite and the cement-based permeable crystalline waterproof material in the strong self-repairing cement-based permeable crystalline concrete is different. Combined with the experimental test results in Table 5, it can be seen that when the total weight of the organic modified sepiolite and the cement-based permeable crystalline waterproof material in the strong self-repairing cement-based permeable crystalline concrete accounts for 3.66%, the comprehensive performance of the prepared strong self-repairing cement-based permeable crystalline concrete is better, and when the total weight of the organic modified sepiolite and the cement-based permeable crystalline waterproof material in the strong self-repairing cement-based permeable crystalline concrete accounts for 3-4%, the comprehensive performance of the prepared strong self-repairing cement-based permeable crystalline concrete is the best. When the proportion is too high or too low, the comprehensive performance is reduced.

[0074] Examples 12-13 Example 12 The difference between this embodiment and Embodiment 10 is that when preparing the cement-based penetrable crystallization type concrete with strong self-repairing properties, the preparation parameters of the cement-based penetrable crystallization type waterproof material used are different. The cement-based penetrable crystallization type waterproof material in this embodiment is prepared by Preparation Example 2.

[0075] Embodiment 13 The difference between this embodiment and Embodiment 10 is that when preparing the cement-based penetrable crystallization type concrete with strong self-repairing properties, the preparation parameters of the cement-based penetrable crystallization type waterproof material used are different. The cement-based penetrable crystallization type waterproof material in this embodiment is prepared by Preparation Example 3.

[0076] Table 6 - Experimental test results of Examples 12-13 Result analysis: The difference between Examples 12-13 and Example 10 is that different preparation parameters of cement-based permeable crystalline waterproof materials are used in preparing the strong self-repairing cement-based permeable crystalline concrete. Combined with the experimental test results in Table 6, it can be seen that the strong self-repairing cement-based permeable crystalline concrete prepared in Example 12 has better comprehensive performance.

[0077] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A cement-based permeable crystalline concrete with strong self-repairing properties, characterized in that: The concrete comprises the following raw materials by weight: 450-550 parts of cement; Sand 800-900 parts; 1050-1150 parts of crushed stone; Fly ash 95-105 parts; Silica fume 38-50 parts; 145-160 parts of water; 15-20 parts of water reducing agent; 16-19 parts of stimulant; 3-4.5 parts of defoaming agent; 13-17 parts of shrinkage reducing agent; 7-9 parts of ramie fiber; Basalt fiber 11-15 parts; 22-26 parts of CaCO3 whiskers; 20-30 parts of organic modified sepiolite; 60-90 parts of cement-based penetrating crystalline waterproof material.

2. The strong self-repairing cement-based permeable crystallized concrete according to claim 1, characterized in that: The weight ratio of the organic modified sepiolite to the cement-based permeable crystalline waterproof material is 1:(2.7-3.4).

3. The strong self-repairing cement-based permeable crystallization concrete according to claim 1, characterized in that: The weight ratio of the organic modified sepiolite to the cement-based permeable crystalline waterproof material is 1:

3.

4. The strong self-repairing cement-based permeable crystallized concrete according to claim 1, characterized in that: The total weight of the organic modified sepiolite and the cement-based permeable crystalline waterproof material accounts for 3-4% of the total weight of the concrete.

5. The strong self-repairing cement-based permeable crystallization concrete according to claim 1, characterized in that: The preparation method of the organic modified sepiolite is as follows: A1. After drying the sepiolite at 110-150° C. for 10-20 hours, the mixture is placed in a thoroughly dried and anhydrous reactor, and then anhydrous ethanol is added. The stirring rate is controlled at 300-650 rpm, and the temperature is raised and kept constant at 50-80° C. Then 3-aminopropyltrimethoxysilane is added. The ethanol in the reactor is kept under condensation and reflux. The reaction is stirred at a constant temperature for 6-10 hours, and then centrifuged. The obtained solid is placed in a vacuum oven and dried at 40-55° C. for 8-13 hours to obtain organosilicon-modified sepiolite. A2. Place the organosilicon-modified sepiolite in a completely dry and water-free vacuum-sealed reactor, continuously evacuate the reactor to maintain the pressure in the reactor within the range of 0.095-0.1MPa, and maintain the negative pressure for 13-20 hours. Then, inject epoxysilane into the reactor by means of the negative pressure. After the epoxysilane completely immerses the organosilicon-modified sepiolite in the reactor, stop injecting epoxysilane. After standing in a sealed state for 4-9 hours, transfer the material in the reactor to a sealed and dry centrifuge, centrifuge, and separate the solid, which is the organic modified sepiolite. Put it into a drying container for temporary storage.

6. The strong self-repairing cement-based permeable crystallization concrete according to claim 1, characterized in that: The cement-based permeable crystalline waterproof material includes the following raw materials by weight: 35-65 parts of silicate cement, 22-28 parts of fly ash beads, 10-20 parts of zeolite powder, 10-15 parts of calcium oxide expansion agent, 10-15 parts of magnesium oxide expansion agent, 8-13 parts of retarder, 8-15 parts of dodecyl ethoxy sulfobetaine, 9-15 parts of meso-tartaric acid, and 612 parts of sodium citrate.

7. The strong self-repairing cement-based permeable crystallization concrete according to claim 6, characterized in that: The preparation method of the cement-based permeable crystalline waterproof material is as follows: B1. Weigh each raw material component according to the raw material ratio and set aside; B2. Add the weighed silicate cement, fly ash beads, zeolite powder, calcium oxide expansion agent, magnesium oxide expansion agent, retarder, dodecylethoxysulfobetaine and meso-tartaric acid into a ball mill and grind evenly to obtain a permeable crystallization type high performance concrete anti-cracking and anti-seepage agent.

8. The strong self-repairing cement-based permeable crystallization concrete according to claim 7, characterized in that: The ball milling process conditions of step B2 are: ball-to-material ratio is 8:1, grinding ball particle size is 10-20 mm, ball mill speed is 150 r / min, and ball milling time is 20-30 min.

9. A method for preparing the highly self-repairing cement-based permeable crystallization concrete according to any one of claims 1 to 8, characterized in that: The method for preparing the concrete comprises the following steps: S1, divide the water into four equal parts; and mix the first part of water with cement, sand, gravel, fly ash, silica fume, CaCO3 whisker, organic modified sepiolite, and cement-based permeable crystalline waterproof material to obtain a first mixture; S2, the second portion of water is mixed with the activator, and the first portion of the mixture prepared in step S1 is added, and then ramie fiber and basalt fiber are added and mixed evenly to prepare the second mixture. S3, mixing the third portion of water with the water reducing agent, adding the mixture to the second portion of the mixture and mixing evenly to obtain a third mixture; S4. Evenly mix the fourth portion of water with the defoamer and the shrinkage reducer, and add the mixture to the third portion of the mixture, mix evenly to obtain a concrete mixture, and cast and cure the concrete mixture to obtain a self-repairing cement-based permeable crystalline concrete.

10. The method for preparing the cement-based permeable crystallization concrete with strong self-repairability according to claim 9, characterized in that: The curing is as follows: first, the curing time is 7-10 days under the conditions of temperature of 20-30°C and humidity of 80-90%, and then the curing time is at least 21 days under the conditions of temperature of 23±2°C and humidity of 50-60%.

Citation Information

Cited By

  • Anti-cracking concrete and preparation method thereof

    CN120349144A